Pulmonary vasoreactivity testing in diagnosis and prognosis of pulmonary hypertension - MUTLU, BÜLENT (TURKISH SOC CARDIOLOGY, 2010)
Right heart catheterization (RHC) is required for confirmation of the diagnosis of pulmonary hypertension (PH) and to asses the prognosis and etiology. Pulmonary vasoreactivity testing (PVT) is one of the most crucial parts of RHC especially in the suitable patient subsets of pulmonary arterial hypertension (PAH) defined by the most recent guidelines. PVT has substantial importance in defining the most appropriate treatment modality. The aim of this review is to provide a comprehensive review of the literature about PVT and the agents used in PVT, to emphasize the importance of this procedure when done with correct indications with a correct technique and to contribute in the accurate management of PH patients. (Anadolu Kardiyol Derg 2010; 10: Suppl 1; 43-9)
Keywords: Pulmonary hypertension; vasodilator agents; pulmonary artery/drug effects; nitric oxide; epoprostenol; adenosine; INHALED NITRIC-OXIDE; CALCIUM-CHANNEL BLOCKERS; LONG-TERM RESPONSE; ARTERIAL-HYPERTENSION; INTRAVENOUS SILDENAFIL; EPOPROSTENOL THERAPY; VASODILATOR THERAPY; SYSTEMIC-SCLEROSIS; PROSTACYCLIN; SURVIVAL